Breaking Motherhood’s Rules: Play and Reproduction in Gabriela Wiener’s Nueve lunas (2009) - Albarrán Caselles, Olga (Revista Canadiense de Estudios Hispánicos, 2022)
This article analyses Nine Moons (2009), by the Peruvian writer Gabriela Wiener, in relation to the concept of play in the creation of the novel, the development of the protagonist as a mother, as well as the dismantling of normative notions of motherhood. Although motherhood as a patriarchal institution is, according to Adrienne Rich, full of norms that oppress women, whether they are mothers or not, it can also be a site of (possible) resistance. I argue how through play Nine Moons separates motherhood from natural processes and exposes its constructed quality, restoring independence and autonomy to the process of gestation.